Effect of Interaction and Rocking Motion on The Earthquake Response of Buildings - Gholamreza Havaei (Iranian Society of Structrual Engineering (ISSE), 2015)
Usually structures are designed under codes based on the assumption that the soil stiffness is infinite, so the foundation rests firmly on the soil. In many cases, the overturning moment due to the lateral forces may exceed the resisting moment due to the gravity forces. Thus, this may cause a foundation uplift because in reality the soil stiffness is not infinite and the structure stands up under gravity forces. The phenomenon of foundation uplifting and its impact on the soil are known as the rocking motion.This study investigates the influence of the rocking motion and interaction by the yielding base plates on the nonlinear behavior of steel structures under dynamic analysis. More specifically, Three- five and seven -storied structuresare designed with ordinary ductility, then the structuresare analyzed in rigid and deformable base plate cases with using the ABAQUS software.The results show that the rocking motion and Interaction decrease the response of buildings such as the base shear, the axial force of columns and the strain energy but also increase the natural period.